Functional characterization of common BCL11B gene desert variants suggests a lymphocyte-mediated association of BCL11B with aortic stiffness. (November 2018) - Maskari, Raya; Hardege, Iris; Cleary, Sarah; Figg, Nicki; Li, Ye; Siew, Keith; Khir, Ashraf; Yu, Yong; Liu, Pentao; Wilkinson, Ian; O'Shaughnessy, Kevin; Yasmin,
Abstract The recent genome-wide analysis of carotid–femoral pulse wave velocity (PWV) identified a significant locus within the 14q32.2 gene desert. Gene regulatory elements for the transcriptional regulator B-cell CLL/lymphoma 11B (BCL11B) are within this locus and an attractive target for the gene association. We investigated the functional impact of these gene desert SNPs on BCL11B transcript in human aorta to characterize further its role in aortic stiffness. To do this, we used a large repository of aortic tissues (n = 185) from an organ transplant program and assessed ex vivo stiffness of the aortic rings. We tested association of three lead SNPs from the GWAS meta-analysis with ex vivo aortic stiffness and BCL11B aortic mRNA expression: rs1381289 and rs10782490 SNPs associated significantly with PWV and showed allele-specific differences in BCL11B mRNA. The risk alleles associated with lower BCL11B expression, suggesting a protective role for BCL11B. Despite strong association, we could not detect BCL11B protein in the human aorta. However, qPCR for CD markers showed that BCL11B transcript correlated strongly with markers for activated lymphocytes. Our data confirm the significance of the 14q32.2 region as a risk locus for aortic stiffness and an upstream regulator of BCL11B. The BCL11B transcript detected in the human aorta may reflect lymphocyte infiltration, suggesting that immune mechanisms contribute to the observed association of BCL11B with aortic stiffness.